Seven new species and one new variety of Valeriana (Valerianaceae) from Mexico - Barrie, Fred R. (Instituto de Ecología, A.C., 2003)
Seven new species of Valeriana endemic to Mexico are described and illustrated. Valeriana naidae Barrie is a suffrutescent, simple-leaved dioecious vine similar to V. subincisa Benth. Valeriana otomiana Barrie, V. zapotecana Barrie, V. chiapensis Barrie, V. moorei Barrie and V. rzedowskiorum Barrie are tap-rooted, perennial herbs. Valeriana tzotzilana Barrie is a biennial herb, endemic to Chiapas. The subspecies V. urticifolia var. scorpioides (DC.) Barrie is proposed, based on V. scorpioides DC. Additionally, a nomen novum, V. oaxacana Barrie, is proposed to replace the illegitimate name V. affinis M. Martens & Galeotti. A key to all species known to occur in Mexico is provided.